Promotion of Myelopoiesis in Myelosuppressed Mice by Ganoderma lucidum Polysaccharides - Zhu, Xiao L.; Liu, Ji H.; Li, Wei D.; Lin, Zhi B. (Frontiers in Pharmacology, 2012)
Ganoderma lucidum polysaccharides (Gl-PS) exhibit potent immunomodulating effects. Immunomodulation plays an important role in hematopoiesis. To investigate the mechanism by which Gl-PS promote myelopoiesis during myelosuppression induced by cyclophosphamide, mice were injected intraperitoneally (i.p.) once daily with 2.5 mg/kg of Gl-PS or with vehicle (i.e. sterile physiological saline) as negative controls for 10 days and were treated i.p. once daily with cyclophosphamide (100 mg/kg) on days 2 through 4. In the present study, we demonstrated that Gl-PS selectively bind to bone marrow stromal cells, stimulate the secretion of hematopoietic growth factors and enhance the clonogenic activities of hematopoietic and stromal cells to promote hematopoiesis.